Pengaruh Pengetahuan Keuangan, Risk Tolerance Terhadap Investasi Saham, Dimoderasi Gender - Indah Yuni Kurniawati S (UMSurabaya Publishing, 2020)
This study aims to determine the effect of financial knowledge and tolerance on stock investment decisions (corporate self-image, reference information and financial information), with data analysis techniques using SEM on WarpPLS, there are 112 respondents with those in accordance with this study. Based on the results of the study, financial knowledge has a significant negative effect on the company's self-image and referral information, but a significant positive effect on financial information. Risk tolerance has only a significant positive effect on financial information and does not have a significant effect on corporate self-image and referral information. Gender cannot moderate the effect of risk tolerance on stock investment decisions. Keywords : stock investment, knowledge, risk tolerance